Comparative Effectiveness of Robo Advisors and Human Planners in AI-Based Financial Planning - Nida Hopia; Anton Budiyono (IJSM, 2026)
Advances in artificial intelligence (AI) technology have introduced robo-advisors as a modern alternative in financial planning. This article conducts a comparative analysis of the effectiveness of AI-based robo-advisors and conventional human financial planners in optimizing individual financial planning. Using a literature review approach and analysis of secondary data from various reliable sources (Grand View Research, Morningstar, Carlson School of Management, Financial Planning Association, Condor Capital, and others), this study evaluates key dimensions of effectiveness, including: investment return performance, fee structure, adoption rates, client satisfaction, and the ability to manage financial complexity. The study’s findings indicate that robo-advisors excel in cost efficiency (a fee of 0.25% vs. 1.00% of AUM), return consistency (7%–9% per year for moderate portfolios), and the elimination of behavioral biases, particularly during periods of market volatility such as the COVID-19 pandemic. Conversely, human financial planners have significant advantages in emotional intelligence, complex financial planning, and providing emotional value to clients. A hybrid model integrating both appears to be the future direction of the industry, with a 60.7% share of the global market by 2024. The implications of this research are relevant for the development of Sharia fintech strategies and the improvement of financial literacy in Indonesia